Jawabanmu

2014-05-21T22:01:41+07:00
L i m  √(2+x) - √(2 - x)    =  l i m  (√(2+x) - √(2 - x)) (√(2+x) +√(2 - x) )
x⇒0            x                      x⇒0              x               (√(2+x) + √(2 - x))
                                     =  l i m   2 + x - 2 + x
                                         x⇒0    x(√(2+x) + √(2 - x))
                                     =  l i m              2x                  
                                         x⇒0  x(√(2+x) + √(2 - x))
                                     = l i m             2                 
                                        x⇒0  √(2+x) + √(2 - x)
                                     =         2           
                                           √2  +  √2
                                     =   2    
                                         2√2
                                     = 1/2 √2




1 5 1